Long-term survey of intertidal rocky shore macrobenthic community metabolism and structure after primary succession - Migné, Aline; Bordeyne, François; Davoult, Dominique (Peer Community Journal)

(untitled)
Ecological succession involves the transition from opportunistic ephemeral species, which display a minimal variation in functional traits, to slow growing, more functionally diverse, perennial species. The present study aimed in measuring the functional effect of changes in the community structure through succession and to compare the timing of successional sequences in communities dominated by canopy-forming algae established at two levels of the emersion gradient in a rocky shore. Granite slabs were set at two tidal levels, in the Fucus vesiculosus and F. serratus areas, in February 2013. Communities settled on the slabs during the first year exhibited low Fucus density (≈ 6 ind m-2), low taxa richness (≈ 17 taxa) and low metabolic activity (gross primary production, GPP, about 100 mg C m-2 h-1) at both levels. Communities established on the slabs were similar to the surrounding communities for the 5 and 3 following years in the F. vesiculosus and F. serratus area respectively. Communities were then characterized by high Fucus density (≈ 35 and 67 ind m-2), high taxa richness (≈ 26 and 39 taxa) and high metabolic activity (GPP ≈ 350 and 550 mg C m-2 h-1). However, Fucus populations did not persist on slabs on which communities turned into limpet dominated, with low Fucus density, low taxa richness and low metabolic activity. 10 years after the slabs setting, limpet densities averaged 34 and 92 ind m-2. Given the long life-span of Fucus and Patella, the survey needs to be pursued to test for cyclical changes of dominance.